Organizational impact of faculty development programs on the medical teacher's competencies - Mahla Salajegheh (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Faculty development programs as useful approaches for organizational development improved competencies in faculty members which assist them to cope with workload and environment changes. Evaluating organizational development for faculty development programs provides insight into the impact of these programs on system development. The aim of present study was conducted to study the organizational development for faculty development programs at Kerman University of Medical Sciences. MATERIALS AND METHODS: This analytical and cross-sectional study was conducted between October and December 2020. The organizational development for faculty development questionnaire was sent to a simple random sampling of 100 faculty members who had been participated in the "Medical Education Fellowship" program. The data were analyzed using descriptive statistics including independent sample t-test, one-way ANOVA, and post hoc, using version 24.0 of SPSS. RESULTS: The response rate was 82%. Most of the faculty highly agreed that the "Medical Education Fellowship" program had produced organizational development. The score of the "Development and sustaining faculty development programs" domain (mean = 3.35, standard deviation [SD] =0.96) was higher than "Development and innovation in teaching and learning process" (mean = 3.31, SD = 0.74). CONCLUSIONS: Specific characteristics of the organizational development process for faculty development programs in health profession education were recognized. The findings emphasized on the importance of these interventions on creating developments in the broader community system.